Evolution of Gaussian wave packets in capillary jets - Garcia, FJ; Gonzalez, H; Gomez-Aguilar, FJ; Pita, A; Castrejon-Pita, JR (American Physical Society, 2019)
A temporal analysis of the evolution of Gaussian wave packets in cylindrical capillary jets is presented through both a linear two-mode formulation and a one-dimensional nonlinear numerical scheme. These analyses are normally applicable to arbitrary initial conditions but our study focuses on pure-impulsive ones. Linear and nonlinear findings give consistent results in the stages for which the linear theory is valid. The inverse Fourier transforms representing the formal linear solution for the jet shape is both numerically evaluated and approximated by closed formulas. After a transient, these formulas predict an almost Gaussian-shape deformation with (i) a progressive drift of the carrier wave number to that given by the maximum of the Rayleigh dispersion relation, (ii) a progressive increase of its bell width, and (iii) a quasi-exponential growth of its amplitude. These parameters agree with those extracted from the fittings of Gaussian wave packets to the numerical simulations. Experimental results are also reported on near-Gaussian pulses perturbing the exit velocity of a 2 mm diameter water jet. The possibility of controlling the breakup location along the jet and other features, such as pinch-off simultaneity, are demonstrated.